Indigenous mycorrhizal fungi from Argentina increase Zn nutrition of maize modulated by Zn fertilization - Aztiz Imaz, Patxi (2014)
The effect of nitrogen (N), phosphorous (P), sulfur (S) and zinc (Zn) fertilization on arbuscular mycorrhizal colonization (AMC), nutrition and growth of maize under contrasting tillage management was assessed in a field trial. The effect of Zn fertilization (+Zn: 1.67 mg Zn kg-1 , -Zn: 0.33 mg Zn kg-1 ), and inoculation with four consortium with arbuscular mycorrhizal fungi (AMF) indigenous of two sites of Buenos Aires, Argentina under contrasting managements(Agricultural and Pristine), on arbuscular mycorrhizal colonization (AMC), nutrition and growth of maize was assessed in a greenhouse trial. Zinc fertilization did not affect growth or AMC under field conditions, but in greenhouse, highest dose of Zn depressed AMC. Zinnc application in greenhouse at a reduced dose resulted in symptoms of deficiency which were translated in reduced plant growth but highest mycorrhizal response (MR). The inoculum from Balcarce Agricultural (indigenous from a site with about 19 mg P kg-1 and 0.5 mg Zn kg-1 ) resulted in the highest AMC and MR in both Zn uptake and dry matter production. The inoculum from Coronel Dorrego Pristine (indigenous from a site with about 8 mg P kg-1 and 2.2 mg Zn kg-1 ) was the lowest efficient. We hypothesized that certain soil characteristics could be used to select potentially beneficial inocula to compensate Zn deficiencies in maize.